a) 4.5 + x = 13
x = 13 - 4.5
x = 8.5
b) 5x = 7/:5
x = 1.4
c) 1/3x = -4/*3
x = -12
d) 3 - x = - 2
- x = 1/*(-1)
x = -1
e) 7x + 8 - 6x - 4 = 12
7x - 6x = 12 - 8 + 4
x = 8
f) 8 - 9x - 5 + 5x - 3 = 20
-9x + 5x = 20 - 8 + 5 + 3
-4x = 20/:(-4)
x = -5
g) 3x + 1 = 4
3x = 3/:3
x = 1
h) 3x - 5 = 4
3x = 9/:3
x = 3
i) 4 - 2x = -2
-2x = -6/:(-2)
x = 3
j) 8 - x = 3
8 - 3 = x
5 = x
k) 4*3x - 7 = 8
12x = 15/:12
x = 1.25
m) 8x-3x/2 = 10
2.5x = 10/:2.5
x = 4
n) 2/5x + 6 - x = 9
-3 = x - 2/5x
-3 = 3/5x /*5
-15 = 3x/:3
-5 = x